Computer Self-Efficacy, Work Stress, and Burnout in Gen Z in Mentoring Communities - Hartono, Nadia; Prapunoto, Susana (Asian Journal of Social and Humanities, 2024)
Currently, awareness of mental health has begun to grow among Generation Z. Mental health is very important considering that poor mental health can affect work performance and health. In the current era, Gen Z has started to become the majority in the world of work, so it is very important for Gen Z to be able to adapt to the world of work to prevent burnout. Burnout has many causes, including the inability to manage stress and also low self-efficacy. The purpose of this research is to determine the effective contribution of computer self-efficacy and work stress to burnout in Gen Z in the Mentorin community. The method used in this research is quantitative research with multiple linear regression analysis. Based on the research that has been carried out, it was found that computer self-efficacy and work stress are significant predictors on burnout.